The Norton anthology of English literature [expanded] - Greenblatt, Stephen 1943-; Abrams, M. H. (Meyer Howard) 1912-2015 (W.W. Norton, 2012)
The ninth edition offers more complete works, more teachable groupings than ever before and the apparatus teachers trust. Read by more than 8 million students, The Norton Anthology of English Literature sets the standard. New longer texts include: 'Sir Gawain and the Green Knight' in Simon Armitage's new translation, Sidney's 'Defense of Poetry', Wycherley's 'The Country Wife', Joyce's 'Portrait of the Artist as a Young Man', Woolf's 'Mrs Dalloway' and Beckett's 'Waiting for Godot' (exclusive to Norton).